The flow of baiano cotton and its logistic barriers: an economic and comparative study between the port of Santos x the port of Salvador - Mateus, Matheus Henrique da Silva (2021)
Competitiveness is an important factor for the global trade and companies, over the years, have been seeking new alternatives to improve their procedures. Logistic processes have been the key to achieve the company goals and rise competitiveness to a higher level. Brazil is a big country, with some internal logistic obstacles that interfere in its international trade result. In this paper, we present the process of exporting cotton from Bahia and the problems of this supply chain. The main objective is to show logistical obstacles in Bahia's cotton trade and propose solutions to this problem by describing the supply chain, showing the port's structure and demonstrating the logistical and economical viability of using Salvador port as an alternative to Santos port.